Design and Development of a Water Separation Process in Cold-Pressed Coconut Oil Fermentation - Kingkaew, Ratsawat; Ruayruay, Wassa; Krainara, Adisorn; Sudsomboon, Weerayute; Pansrinual, Weeraphol; kaewmai, Roihathai (Academic Journal of Industrial Technology Innovation, 2023)
This research aims to design and develop a process of water separation in coconut oil fermentation to prevent the rancidity in coconut oil by using the fermentation from coconut milk. The developed method can separate the fermented water from the coconut oil before the layer of the coconut oil is formed in the fermentation process. The results of 10 experiments from fermenting 5,000 grams of coconut milk showed that the proposed method can separate 3,475 grams of fermented water, which were 69.50% of total, and it can extract 856 grams of coconut oil, which were 17.12% on average. In addition, the qualification test results according to Community Product Standard (CMEC 670/2547) was within the standard.